Seasonal variation and positional differences in anthropometry, strength, and power characteristics in English Premiership women's rugby union players - Yao, X.; Austerberry, A.; Bishop, C.; Wilson, L.; Chiang, C.-Y.; Turner, A. (The Journal of Strength and Conditioning Research, 2024)
Women's rugby is a collision sport that relies heavily on body composition and physical characteristics of strength and power to achieve competitive success. Furthermore, the seasonal nature presents a variety of physical challenges that can cause fluctuations in a player's physical development. Therefore, the purpose of this study was to determine the differences in anthropometry, strength, and power characteristics between forwards and backs in women's rugby union athletes in England and to identify changes throughout a season. Forty-seven players were recruited from the English premiership women's rugby during the 2020-2021 season. Players were split into forwards and backs and underwent body composition testing by dual-energy X-ray absorptiometry and strength and power tests (countermovement jump, drop jump [DJ], and isometric midthigh pull) on 3 separate occasions (preseason, midseason, postseason). Overall, forwards had significantly (p < 0.01) higher body mass, fat mass, lean mass [LM], bone mineral content, and take off momentum, and backs had significantly higher (p < 0.01, d > 0.5) jump height, reactive strength, and shorter DJ contact time. When observing seasonal changes, there were statistically significant differences (p < 0.01) or moderate-to-large practical differences (d > 0.5) in LM, reactive strength index modified, time to take-off, and DJ flight time [FT] among forwards when comparing 3 testing time frames. For backs, statistically significant differences (p < 0.01) or moderate-to-large practical differences (d > 0.5) were reported in LM and DJ FT throughout the season. In conclusion, the strength and power testing and characteristics shown in this study could support coaches and junior women's rugby athletes to have a basic understanding of English premiership physical standards.